Effectiveness of triple benefit health education intervention on knowledge, attitude and practice towards malnutrition among adolescent girls, Borno State, Nigeria - Shapu, Charles Ruth (2021)
Addressing the gap in poor knowledge, attitude and practice (KAP) among adolescent girls are important as malnutrition has a negative effect on their future generation. The adolescence phase comes with a rapid increase in height, changes in body composition, mental, reproductive system, and social development. The objectives of the study are to determine knowledge, attitude and practice of adolescent girls towards malnutrition and to develop, validate, implement and evaluate the effectiveness of a Triple Benefit Health Education Intervention to improve knowledge, attitude and practice of adolescent girls towards malnutrition in Maiduguri Metropolitan Council, Borno State, Nigeria. The methodology of this study was conducted in two phases, Phase I was a cross-sectional study while Phase II was a Randomised Control Trial (RCT). Data was collected using KoBo Toolbox in Government Girls College (GGC), Government Girls Secondary School (GGSS), Yerwa Girls Secondary School (YGSS), Zajeri Day Secondary School (ZDSS), Bulabulin Day Secondary School (BDSS), and Shehu Garbai Day Secondary School (SGDSS), 612 respondents were randomly selected based on the inclusion criteria of the study. Among the eligible respondents, 562 consented and were interviewed with a response rate of (92%) for Phase I. Majority of the respondents were in their middle adolescent stage (49.8%), (86.8%) resides in an urban area, while (55%) had a household size of ≥ 9 (nine) family members. Poor knowledge was reported among (80.2%) of respondents, more than half of respondents (57.3%) showed poor attitude, while about (49.5%) had poor practice towards malnutrition. Triple Benefit Health Education Intervention module was developed for Phase II according to the information, motivation and behavioural skills model (IMB). A two-stage random sampling technique was used. First stage four out of the six secondary schools in Phase I was randomly selected and two classes were randomly selected in each grade level/set. A total of 424 respondents were randomly selected and 417 were eligible for participation (208 in the intervention group and 209 in the control group at baseline) using opaque sealed envelopes. Data were collected at baseline, at three and six months post-intervention and follow up using a questionnaire. There was no significant difference in sociodemographic characteristics, knowledge, attitude and practice between the intervention and control group at baseline. There was a significant difference between intervention and control group for knowledge (AOR = 9.595, 95% CI: 6.371 – 14.449, p <0.001; AOR = 14.993, 95% CI: 9.919 – 22.662, p < 0.001), attitude (AOR = 1.949, 95% CI: 1.451 – 2.616, p <0.001; AOR = 2.276, 95% CI: 1.692 – 3.060, p < 0.001) and practice (AOR = 1.545, 95% CI: 1.164 – 2.051, p = 0.003; AOR = 1.422, 95% CI: 1.083 – 1.867, p = 0.011) respectively from baseline to post-intervention and follow up after the Triple Benefit Health Education Intervention. The findings from this study provide evidence for the effectiveness of Triple Benefit Health Education Intervention in improving knowledge, attitude and practice among adolescent girls in Maiduguri Metropolitan Council, Borno State, Nigeria. The study suggests that knowledge, attitude and practice towards malnutrition will reduce the burden of malnutrition, improve healthy lifestyle among adolescent girls and their future offspring.